Modulation of C5A receptor in mammary gland tumour by EP54 and PMX205 peptides - Kosni, Nurneqman Nashreq (2015)
Drug resistance has become the main issue in cancer therapy field. This situation causes the increasing number of cancer related disease in the world. The usage of complement 5a has become a new method of therapy against cancer by following agonist-antagonist treatment. This project was mainly about the agonist (EP54) and antagonist (PMX205) modulate the expression of C5aR causing the regression of mouse mammary gland tumour. The objectives of this project were to determine the expression of C5a receptor on 4T1 cell line, to determine the mechanism of mouse mammary gland tumour cell death after treatment with respective peptides, determine the effect of the peptides on mouse mammary gland tumour cell, and to determine the effect of EP54 and PMX205 on the liver and kidneys of mice with 4T1-induced mammary gland tumour. Several methods were conducted such as immunoflourescence staining, PCR, ELISA (TNF-α, VEGF, Caspase 3 and C5a),acridine orange and propidium iodide double staining and serum biochemical analysis. The results showed that the presence of C5a receptor on 4T1 cell line was based on the immunoflourescence staining and PCR. The presence of the receptor showed that the 4T1 cell was suitable to be used with those peptides. The mechanism was determined by using ELISA. Based on ELISA results, it showed that the apoptosis becomes the underlying pathway that is used in mammary gland tumour regression for both environments in vitro and in vivo. These findings showed that the apoptosis is an important process involved in most organisms for survival. In order to validate the findings, acridine orange/propidium iodide staining (AO/PI) and cell viability assay were conducted. Besides, tumour measurements also were used as to validate the mechanism proposed. Both peptides showed capability to present apoptosis based on the AO/PI result. While in the cell viability assay (Alamar Blue & MTT) in which it represents data in vitro, it showed that PMX205 showed greater potential in treating the cancer compared to EP54 group. In Alamar Blue assay, the result showed that the absorbance PMX205 was lower compared to EP54 group. Similar trend could also be found from the MTT assay. Tumour measurement recorded from the in vivo experiment, shows that the size of tumour decreased in EP54 group whereas the PMX205 group, the tumour maintain its own size. In the serum biochemical analysis,no significant effects were obtained on the liver and kidney of the animal. Based on these results, it showed that EP54 and PMX205 could modulate the expression of C5aR causing the regression of mouse mammary gland tumour. Apoptosis was the underlying mechanism involved during the treatment and the treatment did not produce significant effects on the organ of the animal.